The Impact of Product Quality towards Sales at PT. Pentaco Makmur Medan - Ester; Ali Syah Putra; Edward Harnjo; Eddy Gunawan; Javerson Simamora (Universitas Muhammadiyah Palu, 2024)
This research explains a conceptual model that elucidates the factors that influence the impact of product quality at PT. Pentaco Makmur Medan and how this information can be effectively used for business development and sustainability. This study is a review that identifies sales as the dependent variable, through a systematic review of online literature sources. Three independent variables were then identified viz. product features, service value chain and consumer behaviour. The research objectives and research questions were defined to assess the influence of the independent variables on customer satisfaction. It was identified that critical product features identified and shared during early stages of product development influences customer satisfaction by reducing product failures. Furthermore, customer satisfaction mediates improved service value leading to loyalty and finally, consumer behaviour in sharing experiences extends the product's life and influences customer satisfaction